The Role of Health Education on the Level of Knowledge of Contact Dermatitis in the Elderly - Hera, Renata Evania; Damayanti; Lilik Djuari; Ema Qurnianingsih (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Contact dermatitis is a skin condition resulting from exposure to external substances that provoke allergic or irritant reactions. Individuals aged 60 and older are particularly susceptible to this condition due to the physiological changes in their skin accompanying aging. Purpose: To analyze the role of education regarding contact dermatitis in the elderly. Methods: The sampling technique used in this study is a total sampling technique using the pre-experimental one-group method, and presented the results in an analytical descriptive format. Result: The study demonstrated a significant impact of the educational intervention on contact dermatitis regarding the knowledge levels of the research subjects. Analysis using the Wilcoxon test revealed a significance value of 0.001 (p < 0.05). This finding indicates that the educational intervention resulted in a notable improvement in knowledge from before to after it. Conclusion: There is a significant impact of the educational intervention on the knowledge levels of the elderly, as observed before and after the intervention.